2015
DOI: 10.1177/1087054715586571
|View full text |Cite
|
Sign up to set email alerts
|

Is ADHD Really Increasing in Youth?

Abstract: Time-trend national surveys of ADHD in youth over the last two decades reveal consistent increases in its diagnostic prevalence, whereas time-trend findings for individual ADHD-related symptoms remained relatively stable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 73 publications
2
28
0
Order By: Relevance
“…Significant increases in the number of patients receiving medications for ADHD have been reported in several countries in recent years (Safer et al 1996;Hodgkins et al 2011;Chien et al 2012;Treceno et al 2012;Oner et al 2014;Ponizovsky et al 2014;Visser et al 2014;Stuhec et al 2015), which is consistent with our findings. However, the higher number of patients receiving ADHD medication is naturally related to the higher number of patients diagnosed with ADHD.…”
Section: Use Of Adhd Medication and Whether Youths Are Overmedicated supporting
confidence: 93%
See 2 more Smart Citations
“…Significant increases in the number of patients receiving medications for ADHD have been reported in several countries in recent years (Safer et al 1996;Hodgkins et al 2011;Chien et al 2012;Treceno et al 2012;Oner et al 2014;Ponizovsky et al 2014;Visser et al 2014;Stuhec et al 2015), which is consistent with our findings. However, the higher number of patients receiving ADHD medication is naturally related to the higher number of patients diagnosed with ADHD.…”
Section: Use Of Adhd Medication and Whether Youths Are Overmedicated supporting
confidence: 93%
“…This implies that the prevalence rates of ADHD, determined by face-to-face assessments of community youths, had not changed significantly over time. Therefore, the ascending trend of numbers of patients being diagnosed with ADHD may only reflect the increase in patients seeking medical care, but should not be viewed as an increase of youths with ADHD (Safer, 2015). The most reliable estimate of the prevalence of ADHD in Taiwan reported that ADHD affects 7.5% of school-aged children (Gau et al 2005).…”
Section: Prevalence Of Adhd and Whether It Is Overdiagnosedmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the different study populations and different methods used, these previous studies all point toward increasing rates of clinically diagnosed and treated ADHD. However, it has been suggested that even though rates of clinically diagnosed ADHD have increased, ADHD symptoms seem to have been stable over time (Safer, ), which suggests that the increase seen in studies based on clinical diagnosis does not necessarily reflect an increase in the underlying ADHD phenotype. Changes in quality of data, and administrative changes in reporting diagnoses, are plausible alternative explanations.…”
Section: Introductionmentioning
confidence: 99%
“…First, it can arise due to the problem of overdefinition,15 that is, lowering the threshold for a disease, by expanding the disease definition to include people with ambiguous or very mild symptoms without evidence that doing so improves patients’ health overall and in the longer term 16 17. Second, overdiagnosis may also be caused by overdetection4 18 (eg, screening children at young ages for behaviour problems), and third by the medicalisation of some behaviour patterns (eg, those typical of relatively younger school children) 19. Other factors may also have played a part.…”
Section: Introductionmentioning
confidence: 99%